Holding on: family and fatherhood during incarceration and reentry - McKay, Tasseli (University of California Press, 2019)
Returning incarcerated fathers to the family -- "Always having hope" : what we (didn't) know about fatherhood and incarceration -- "I do, but I don't, know where we are" : couple relationships during incarceration and reentry -- "None of the above" : unraveling complexity, ambivalence, and the limitations of research to understand abuse in justice-involved couples -- To be in jail for 10 years, change ain't going to happen overnight" : operationalizing reentry success -- "A breakthrough type of thing" : quantifying (and qualifying) the impact of family strengthening programs during incarceration and reentry -- On the horizon : the social science of incarceration and family life.